Antioxidant and â-glucan content in oats as affected by soil type and N-level - Fogelfors, Birgitta Mannerstedt; Sohl, Jonathan; Alström, Sadhna; Peterson, David M (MTT, 2004)
Avenanthramides, tocols and -glucans in oats are substances that can positively influence human health. Their content in the oat grain is affected by genotype and environmental factors. This study was initiated to clarify the role of the soil type and N-level on grain antioxidant and -glucan content. Two cultivars, Freja (6% oil) and Matilda (10% oil), were grown in 2003 outdoors in boxes containing soils from two Swedish sites, Jönköping (J) and Köping (K), in four replicates. Two levels of N fertiliser were applied, 120 and 240 kg/ha. The soils were analysed for chemical composition. Grain yield and harvest index (HI) were determined. Grains were dehulled and analysed for content of avenanthramides, tocols, -glucan, oil and protein. The overall content of avenanthramides in the oat samples was very high. - Glucan data were not yet analysed at the time of abstract preparation. There were no significant differences in grain composition between soils. Significant differences were found between N-levels for content of the avenanthramides 2c, 2f, total avenanthramides, and protein. Cultivars differed for content of avenanthramides, 2p, 2f, total avenanthramides, -tocopherol, total tocols, protein, and oil. Moreover, the cultivar x N-level interaction was significant for content of -tocopherol, -tocotrienol, total tocols, protein, and oil. Yield and HI were significantly affected by soil, N-level, and cultivar. The results indicate that differences in type and composition of these soils had little effect on content and composition of avenanthramides, tocols and oil in oat grains. However, other soils that may have greater differences in type and composition could affect grain composition as well as yield and HI. From the two studies of 2003 combined, it may be concluded that environmental factors other than soil type, e.g. N-level, climate, are more important in controlling grain composition.
Keywords: Ka; avenanthramides; tocols; protein; oil; soil composition